Experimental Study on Mechanical Properties of Briquette Coal Samples with Different Moisture Content - Wang Haidong; Tao Yang; Wang Deyue; Sun Xin; Gao Jiahui (Geofluids)
Coal seam water injection is an important technical method to prevent and control coal and gas outburst and other disasters. Water can soften coal and change its mechanical properties. In order to study the mechanical properties of coal samples with different moisture content, briquette coal samples with five moistures content (4%, 6%, 8%, 10%, and 12%) were selected to carry out triaxial compression tests under different confining pressures (0.1, 0.2, 0.4, 0.8, and 1.2 MPa). Then, the mechanical response mechanism of the water-bearing briquette coal was analyzed. The results show that the slope of the linear elastic stage of the stress-strain curve gradually decreases with the increase of moisture content. Water-bearing coal exhibits strain strengthening characteristics under high confining pressure, which transforms the water-bearing coal from brittle to ductile state. The peak stress under different moisture content conditions shows a linear relationship with the confining pressure. The internal friction angle decreases linearly with the increase of moisture content. The cohesion varies parabolically with the increase of moisture content and reaches the maximum value when the moisture content is 8%. The coal body with moisture content between 7% and 9% has a high bonding force, which is beneficial to the consolidation of the coal body. Therefore, ensuring a reasonable moisture content of coal through coal seam injection can provide a basis for preventing coal and gas outburst.